Clinical Evaluation and Management for Lisfranc Injury with Cuneiform Fracture. Issue 4 (16th October 2019) - Gu, Wenqi; Xu, Hongwei; Shi, Zhongmin; Zhang, Hongtao; Mei, Guohua; Xue, Jianfeng; Zou, Jian; Wang, Xiaokang
Category: Midfoot/Forefoot Introduction/Purpose: To summarize and evaluate the treatment and clinical outcome of Lisfranc injury with cuneiform fracture retrospectively. Methods: From January 2014 to December 2017, totally 128 cases of Lisfranc injury with cuneiform fractures were treated in our department including 78 cases of male and 50 cases of female with an average of 42.2 ±10.5 years old . There were 60 left feet and 68 right feet, two of which were suffered from an open injury. From the CT scanning, The avulsion fracture of cuneiform was seen in 48 cases, while other 80 cases were cuneiform body fractures or comminuted fractures. An open reduction and internal fixation were undergone after the improvement of soft tissue condition. Final clinical outcome were evaluated by VAS score and AOFAS midfoot score. Complication were also recorded. Results: 9 cases suffered from an early stage of wound and soft tissue complication, who were cured by a dressing change. All cases were followed for a mean of 16.3 months (range: 6-36 months). The plain radiograph demonstrated that the bone union were achieved on the 12.8±1.3 weeks (range: 11-16 weeks) post-operatively on average. The VAS score at the final follow-up was 1.8±1.7 (range: 0-8), while the AOFAS midfoot score was 81.3±10.4 (range: 35-95). The excellent and good rate was 88.3%. 12 cases of post-traumatic arthritis of midfoot was manifested on the X-ray, five of which underwent a salvage arthrodesis in consequence of the severe symptom and disability. The implant of 49 cases were removed on an average of 13.5 month (9-24 months). Conclusion: The Lisfranc injury is always associated with cuneiform fractures, which should be attached importance to in clinical work. For the simple cuneiform fractures, screw fixation could be performed. The key of management is the restoration of intercunceiform joint. And an anatomical alignment and stable fixation of midfoot may facilitate an acceptable clinical outcome.